Leisure physical inactivity and common mental disorders in Primary Health Care workers (Research, Society and Development, 2021)
Objective: To assess the association between leisure-time physical inactivity (IFL) and common mental disorders (CMD) among Primary Health Care (PHC) workers. Methods: Cross-sectional study, carried out with a random sample of 2,136 PHC workers from municipalities in the state of Bahia. The data collection questionnaire included sociodemographic and occupational characteristics, lifestyle and the Self-Reporting Questionnaire. Multivariate analysis was performed using Poisson Regression with robust variance. Results: Prevalences of 22.6% for CMD and 48.2% for IFL were identified. In the bivariate analysis, there was a higher prevalence of CMD in those with IFL (p